Silicon: From the Invention of the Microprocessor to the New Science of Consciousness by Federico Faggin - Pilkington, Rosemarie (Journal of Scientific Exploration, 2021)
I was a little apprehensive about reviewing this book because I know little about engineering or the inner workings of the computer, but in the interest of full disclosure, I wanted to know more about Federico Faggin. Twenty years ago, returning from an afternoon trip during the SSE conference in San Diego, I sat next to him on the bus and mentioned that since we last met I had lost the vision in my right eye, which I was still adjusting to physically and emotionally. He volunteered that he had lost the vision in his left eye when he was a youth in Italy and lightly commented that depth perception, which concerned me, was only an issue for six or seven feet. His admission and attitude were not only a revelation, but an inspiration for me: If this eminent gentleman had made world-changing inventions, was a successful businessman and had a happy social and family life despite monocular vision; I certainly could get on successfully with my life as well. Silicon is the fascinating story of Federico Faggin’s remarkable life, but it is also his personal journey from scientific materialism to an awakening to a deeper level of consciousness. He divides his narrative into his four “lives.” His first life took place in his native northern Italy where he was a brilliant student with a wide range of interests. He became interested in computers and transistors, which had been recently invented and read all he could independently, since it was not taught in his school. His fascination deepened and he got a job with Olivetti where he learned much more than he could have at school and which become pivotal to his subsequent career.